Smallpox Still Haunts Scientists: Results of a Questionnaire-Based Inquiry on the Views of Health Care and Life Science Experts and Students on Preserving the Remaining Variola Virus Stocks. (22nd July 2013) - Srinivasan, Thangavelu; Dedeepiya, Vidyasagar Devaprasad; John, Sudhakar; Senthilkumar, Rajappa; Reena, Helen C.; Rajendran, Paramasivam; Balamurugan, Madasamy; Kurosawa, Gene; Iwasaki, Masaru; Preethy, Senthilkumar; Abraham, Samuel J. K.
Abstract : The World Health Organization (WHO) declared eradication of the dreadful disease "smallpox" in 1980. Though the disease has died down, the causative virus "variola" has not, as it has been well preserved in two high security laboratories—one in USA and another in Russia. The debate on whether the remaining stocks of the smallpox virus should be destroyed or not is ongoing, and the World Health Assembly (WHA) in 2011 has decided to postpone the review on this debate to the 67th WHA in 2014. A short questionnaire-based inquiry was organized during a one-day stem cell meeting to explore the views of various health care and life science specialists especially students on this aspect. Among the 200 participants of the meeting, only 66 had answered the questionnaire. 60.6% of participants who responded to the questionnaire were for preserving the virus for future reference, while 36.4% of the participants were for destroying the virus considering the magnitude with which it killed millions. However, 3% of the respondents were not able to decide on any verdict. Therefore, this inquiry expresses the view that "what we cannot create, we do not have the right to destroy."